2008
DOI: 10.1088/1009-0630/10/2/20
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 4 MV Laser-Triggered Multi-Stage Switch

Abstract: A 22-stage 4 MV laser-triggered multistage multi-channel switch (LTS) was designed according to the hypothesis that the well-proportioned electrical field distribution is helpful in reducing the jitter of delay. Field distribution in the switch section is regulated by a metal field regulation ring and several gradient rings. In order to reduce the jitter further, a SF6/N2 mixture is chosen as the switching medium. The generalized standard deviation of the self-breakdown voltage and the deviation of the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The maximum output energy of the laser is higher than 100 mJ. Each laser is divided into two beams and used to trigger two adjacent switches in the same layer [27,28]. The jitter of the LTGS is less than 1.5 ns.…”
Section: The Pts Facility and Its Full Circuit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum output energy of the laser is higher than 100 mJ. Each laser is divided into two beams and used to trigger two adjacent switches in the same layer [27,28]. The jitter of the LTGS is less than 1.5 ns.…”
Section: The Pts Facility and Its Full Circuit Modelmentioning
confidence: 99%
“…The Z [24], the Primary Test Stand (PTS) [25][26][27][28] and the Angara-5-1 [29] research groups all have used exclusive codes to investigate accelerator power flow by introducing theoretical concepts for magnetic insulation or magnetohydrodynamic (MHD) models for the load [30]. In those codes, an incident wave or equivalent voltage source at the boundaries of the MITL is often used to drive an equivalent circuit thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied the influence of the mixing ratio on t d and σ d in various SF 6 admixture. Previous research has revealed that with rise in j(SF 6 ) the t d and σ d exhibits an increasing trend [6][7][8]. Chen et al [9] reported that σ d can be improved by manipulating the switch gas temperature and by adding a beta emitter such as Kr 85 isotope.…”
Section: Introductionmentioning
confidence: 99%
“…In the Marx based scheme, each facility module will generate a current of 0.4-1 MA. This means that the main switch, for example the laser triggered gas switch (LTGS) [20,21] will suffer very large Coulomb and serious electrode erosion in every shot. Lifetime of the LTGS is estimated to be hundreds of shots, which prevents it being used in rep-rate drivers.…”
Section: Introductionmentioning
confidence: 99%